A methodology for online characterization of the deconsolidation of fiber-reinforced thermoplastic composite laminates. (April 2023) - Amedewovo, Luc; Levy, Arthur; de Parscau du Plessix, Basile; Aubril, Julien; Arrive, Arnaud; Orgéas, Laurent; Le Corre, Steven
Abstract: Pre-consolidated fiber-reinforced thermoplastic laminates often need a secondary manufacturing step such as welding, forming. When a low pressure is applied during the laminate heating stage, porosities can appear in various forms (bubbles, delaminations, etc. ). This is the deconsolidation phenomenon. These porosities significantly deteriorate the mechanical properties of the composites. Usually, deconsolidation is characterized by analysis after processing or by Thermomechanical Analysis (TMA). However, these techniques do not allow online investigation of deconsolidation mechanisms on representative composite laminates. In order to overcome these limitations, a new experimental device has been developed. It allows the online characterization of fiber-reinforced thermoplastic laminate deconsolidation, by continuous measurement of deconsolidation strain of samples with large size (several centimeters in contrast to a few millimeters in TMA) under representative heating conditions. The capability of the setup is illustrated on plate samples made of a high-performance Carbon Fiber (CF) - reinforced thermoplastic (CF/PEKK laminates).